Baby boomers' attitudes to maintaining sexual and intimate relationships in long‐term care. (21st June 2020) - Rahn, Alison; Jones, Tiffany; Bennett, Cary; Lykins, Amy
Abstract: Objectives: Australian aged care policy is wholly focused on individual "consumers" and consequently neglects the needs of dyadic partners. This paper highlights partnered baby boomers' attitudes to maintaining sexual and intimate relationships in residential care. Methods: In 2016, cross‐sectional data were collected using an online survey of partnered baby boomers recruited using social media. Qualitative data were analysed using word frequency, keywords‐in‐context and thematic analysis. Descriptive statistics were generated from quantitative data. Results: There were 168 participants (85% female), aged 51‐71 years. Many reported that remaining together and continuing physical and sexual contact were important in aged care contexts—necessitating private couple's suites, shared beds, access to condoms, lubricants and sexual health professionals. Conclusions: Considerable cultural change will be required to raise residential aged care to the standard expected by some partnered baby boomers. Shifting to a more couple‐centred approach may benefit partnered residents' health and well‐being.